Treatment of taeniasis and cysticercosis with praziquantel and albendazole (Faculty of Medicine Universitas Indonesia, 2005)
Recent methods, doses and results of medical treatment on taeniasis/cysticercosis, a zoo-notic parasitic disease caused by Taenia solium and Taenia saginata are discussed. In cases of cysticercosis T. solium, especially neurocysticercosis the optimal length and dose of albendazole is a course of 8 days with doses of 15 mg/kg/day divided in two times added by 50 mg/day of prednisone in the morning. The drug is effective in almost any location of the parasites for 80-90% of macroscopic cysts seen by imaging studies. For taeniasis a single dose of praziquantel, 10-15 mg/kg achieves cure rates of more than 90%. Side effects such as nausea, headache and abdominal pain are mild. Evaluation of drug treatment is done by clinical, radiological and serological evaluation. In Papua (=Irian Jaya) nine cases with suspected neurocysticercosis, serologically positive, were treated with 1200 mg single dose albendazole for 15 days. Prednisone tablets, three times daily one tablet, 5 mg during 7 days were added. After one year 6 cases were still serologic positive. At the same time praziquantel, 1200 mg, single dose was given to ten cases during 15 days and prednisone tablets, 3 times daily one tablet, 5 mg during 7 days. After one year 5 sero-positive cases were still found. Albendazole and praziquantel are both effective drugs for taeniasis and cysticercosis, with minor side effects. In addition symptomatic treatment should be given if necessary. (Med J Indones 2005; 14:253-7)